The Effect of Problem-Based Learning Model Using Digital Snakes and Ladders on Primary School Pupils' Geometric Reasoning Skills - Fenita Mei Wulandari; Noening Andrijati (Jurnal Pendidikan MIPA, 2026)
Primary school pupils’ ability to reason geometrically remains a challenge in mathematics education, particularly regarding abstract concept angles, which require conceptual understanding and logical reasoning. This situation highlights the need for educational innovations that actively engage pupils and provide more relevant, contextual learning opportunities. The Problem-Based Learning (PBL) model, combined with interactive digital learning resources, is one such strategy. This study aims to examine how implementing the Problem-Based Learning model, supported by a digital snakes-and-ladders game, influences the geometric reasoning skills of Year 3 primary school pupils. The study employed a quasi-experimental, non-equivalent control group design and a quantitative methodology. A total of 54 pupils formed the sample, divided into experimental and control groups. The geometric reasoning ability test and student response questionnaire served as the research instruments. Prerequisite tests (homogeneity and normality), an independent-samples t-test for hypothesis testing, and N-Gain for assessing effectiveness were conducted in SPSS version 27. The geometric reasoning abilities of students in the experimental and control groups differed significantly, according to the research findings, with a significance value of 0.045 (p < 0.05). An effect size analysis using Cohen’s d revealed a moderate effect (d = 0.55), indicating that the intervention had a significant practical impact on pupils’ geometric reasoning skills. The average post-test score of the experimental class was higher than that of the control group, indicating that the use of digital media in PBL had a more beneficial effect on geometric reasoning skills. According to the N-Gain test results, the experimental class showed a high improvement in geometric reasoning ability (0.72), while the control group showed a moderate improvement (0.43). In addition, the pupils demonstrated very positive responses regarding interest in learning, engagement, collaboration, ease of use of the media, conceptual understanding, and geometric reasoning, with an overall average response rate of 97.44%. These results indicate that integrating digital game media with the Problem-Based Learning (PBL) model not only improves learning outcomes quantitatively but also fosters more interactive, contextual, and student-centered learning. Therefore, the use of the PBL model alongside digital snakes and ladders game media can serve relevant alternative learning strategy to help primary school pupils improve their geometric reasoning skills. Keywords: problem-based learning, digital snakes and ladders, geometric reasoning, primary school, mathematics learning.